An Overview of Bioterrorism and Preparedness for Bioterrorism Attack - R.O. , Ekoko (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
In a very horrible and frightening dimension where terrorism has somewhat become the order of the day globally, it is essential that people are enlightened about bioterrorism which is a form of terrorism. The thrust of this paper is on bioterrorism and preparedness in the event of a bioterrorist attack. An overview of bioterrorism was taken and some of the biological agents which can be used for bioterrorism attacks were highlighted. Some historical facts about bioterrorism as well as some diseases which can result from the use of various biological agents were discussed. Preparedness for a bioterrorism attack was discussed with a focus on health facilities and families. Recommendations made include the need to sensitize and educate people about bioterrorism and that all tiers of government, private and public organizations should always have bioterrorism readiness plan in place.